Convergence culture : where old and new media collide - Jenkins, Henry, 1958- (New York : New York University Press, 2006)
Media analyst Jenkins delves beneath the new media hype to uncover the important cultural transformations that are taking place as media converge. He takes us into the secret world of Survivor Spoilers, where avid internet users pool their knowledge to unearth the show's secrets before they are revealed on the air. He shows us how The Matrix has pushed transmedia storytelling to new levels, creating a fictional world where consumers track down bits of the story across multiple media channels. Jenkins argues that struggles over convergence will redefine the face of American popular culture: industry leaders see opportunities to direct content across many channels to increase revenue and broaden markets; at the same time, consumers envision a liberated public sphere, free of network controls. Jenkins explains the cultural shift as consumers fight for control across disparate channels, changing the way we do business, elect our leaders, and educate our children.--From publisher description.
Introduction: "Worship at the altar of convergence": a new paradigm for understanding media change -- Spoiling Survivor: the anatomy of a knowledge community -- Buying into American idol: how we are being sold on reality TV -- Searching for the origami unicorn: The matrix and transmedia storytelling -- Quentin Tarantino's Star wars?: grassroots creativity meets the media industry -- Why Heather can write: media literacy and the Harry Potter wars -- Photoshop for democracy: the new relationship between politics and popular culture -- Conclusion: Democratizing television?: the politics of participation.
Includes bibliographical references (p. 261-278) and index.
Keywords: Mass media and culture -- United States; Popular culture -- United States; Massamedia; Internet